Hybrid lipids, peptides, and lymphocytes: new era in type 1 diabetes research - Hamad, Abdel Rahim A. (J Clin Invest, 2019)
Type 1 diabetes (T1D) results from autoimmune destruction of insulin-producing β cells in islets of Langerhans. Many genetic and immunological insights into autoimmune disease pathogenesis were initially uncovered in the context of T1D and facilitated by preclinical studies using the nonobese diabetic (NOD) mouse model. Recently, the study of T1D has led to the discovery of fatty acid esters of hydroxyl fatty acids (FAHFAs), which are naturally occurring hybrid peptides that modulate inflammation and diabetes pathogenesis, and a hybrid lymphocyte that expresses both B and T cell receptors. Palmitic acid esters of hydroxy stearic acids (PAHSAs) are the most extensively studied FAHFA. In this issue of the JCI, Syed et al. have shown that PAHSAs both attenuate autoimmune responses and promote β cell survival in NOD mice. Given the lack of effective T1D therapies and the paucity of known side effects of PAHSAs, this lipid may have therapeutic potential for individuals at risk for or newly diagnosed with T1D.